S-23-5: TWO-YEAR RESPONSES OF OFFICE AND AMBULATORY BLOOD PRESSURE TO FIRST OCCUPATIONAL LEAD EXPOSURE. (January 2023) - Yu, Yu-Ling; Yang, Wen-Yi; Thijs, Lutgarde; Melgarejo, Jesus; Yu, Cai-guo; Wei, Dong-mei; Wei, Fang-fei; Nawrot, Tim; Zhang, Zhen-Yu; Staessen, Jan
Abstract : Lead exposure causing hypertension is the mechanism commonly assumed to set off premature death and cardiovascular complications. However, at current exposure levels in the developed world, the link between hypertension and lead remains unproven. In the Study for Promotion of Health in Recycling Lead (NCT02243904), we recorded the 2 year responses of office blood pressure (OBP, average of five consecutive readings) and 24 h ambulatory blood pressure (ABP) to first occupational lead exposure in workers newly employed at lead recycling plants. Blood lead (BL) was measured by inductively coupled plasma mass spectrometry (detection limit 0.5 μg/dL). Hypertension was defined according to the 2017 ACC/AHA guideline. Statistical methods included multivariable-adjusted mixed models with participants modelled as a random effect and interval-censored Cox regression. OBP was measured in 267 participants (11.6% women, mean age at enrollment, 28.6 years) and ABP in 137 at two follow-up visits. Geometric means were 4.09 μg/dL for baseline BL and 3.30 for the last-follow-up-to-baseline BL ratio. Fully adjusted changes in systolic/diastolic blood pressure associated with a doubling of the BL ratio were 0.36/0.28 mm Hg (95% confidence interval, 0.55 to 1.27/ 0.48 to 1.04 mm Hg) for OBP and 0.18/0.11 mm Hg (2.09 to 1.74/ 1.05 to 1.27 mm Hg) for 24 h ABP. The adjusted hazard ratios of moving up across hypertension categories for a doubling in blood lead were 1.13 (0.93–1.38) and 0.84 (0.57–1.22) for OBP and ABP, respectively. In conclusion, the 2 year blood pressure responses and incident hypertension were not associated with the BL increase on first occupational exposure.